Mesenchymal Stem Cell-Derived Exosomes Modulate Chondrocyte Glutamine Metabolism to Alleviate Osteoarthritis Progression - Kai Jiang; Ting Jiang; Yang Chen; Xinzhan Mao (Mediators of Inflammation)
Osteoarthritis (OA) had a high incidence in people over 65 years old, and there is currently no drug that could completely cure it. This study is aimed at studying the role of exosomes in regulating glutamine metabolism in the treatment of OA. First, we identified the exosomes extracted from the mouse OA model’s bone marrow mesenchymal stem cells (MSC). In vitro, compared with the control group, the cell apoptosis in the OA group increased, while the cell proliferation of the OA group was suppressed. After exosomal treatment, cell apoptosis and cell proliferation were reversed. Inflammatory factors (TNFα, IL-6), glutamine metabolic activity-related proteins (c-MYC, GLS1), glutamine, and GSH/GSSG were increased in the OA group. The overexpression of c-MYC reduced the therapeutic effect of exosomes. At the same time, we found that chondrocyte functional factors (collagen II, Aggrecan) were improved under the treatment of exosomes. However, oe-c-MYC reversed the therapeutic effect of exosomes. In vivo, we found that the running capacity of the mice in the OA group was reduced, and the cartilage tissue was severely damaged. In addition, TNFα, IL-6, and chondrocyte apoptosis increased, while the metabolism of collagen II, Aggrecan, and glutamate decreased in the OA group. After exosomal treatment, the mice’s exercise capacity, tissue damage, inflammation, and chondrocyte function were improved, and glutamate metabolism was increased. This study showed that exosomes regulated the level of chondrocyte glutamine metabolism by regulating c-MYC, thereby alleviating OA.